2015
DOI: 10.1021/acs.langmuir.5b02414
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Graphene Oxide with Model Cell Membranes: Probing Nanoparticle Attachment and Lipid Bilayer Disruption

Abstract: With the rapid growth in the application of graphene oxide (GO) in diverse fields, the toxicity of GO toward bacterial and mammalian cells has recently attracted extensive research attention. While several mechanisms have been proposed for the cytotoxicity of GO, the attachment of GO to cell membranes is expected to be the key initial process that precedes these mechanisms. In this study, we investigate the propensity for GO to attach to and disrupt model cell membranes using supported lipid bilayers (SLBs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 85 publications
1
83
0
Order By: Relevance
“…It has been reported that the cytotoxicity of GO nanosheets (a few hundred nanometer to a few micrometer) was resulted from the physical damage of cell membrane due to the direct interactions between the cell membrane and GO nanosheets . In contrast, the disruption of model cell membrane induced by the deposition of GO (100–150 nm) could recover because of its self‐healing ability . In addition, Biris and co‐workers demonstrated that the aggregation/agglomeration of graphene nanosheets (100–110 nm) on the cell membrane only partially contributed to their cytotoxicity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the cytotoxicity of GO nanosheets (a few hundred nanometer to a few micrometer) was resulted from the physical damage of cell membrane due to the direct interactions between the cell membrane and GO nanosheets . In contrast, the disruption of model cell membrane induced by the deposition of GO (100–150 nm) could recover because of its self‐healing ability . In addition, Biris and co‐workers demonstrated that the aggregation/agglomeration of graphene nanosheets (100–110 nm) on the cell membrane only partially contributed to their cytotoxicity .…”
Section: Resultsmentioning
confidence: 99%
“…Cell Membrane Integrity : The interactions of layered BP with the model cell membrane, which was fabricated by DOPC vesicles, were monitored by QCM‐D (E1, Q‐Sense, Biolin Scientific, Sweden) . Before the QCM‐D experiments, the gold‐coated crystal sensors were immersed in a solution mixture containing H 2 O, H 2 O 2 (30%), and NH 3 (25%) with the ratio of 5:1:1 at 75 °C for 5 min, and then rinsed with Millipore water, followed by dryness under nitrogen gas stream.…”
Section: Methodsmentioning
confidence: 99%
“…Coating the sensors with molecules such as l-cystine and self-assembled monolayers (SAMs) has also been reported (Yi and Chen, 2013; Liu and Chen, 2015, 2016). The versatility of surfaces provides opportunities for tailoring the surface interaction of SLBs with their substrates; for example, while gold is electrostatically neutral at physiological pH, silica and alumina carry negative and positive charges, respectively.…”
Section: Formation and Characterization Of Slbs Using Qcm-dmentioning
confidence: 99%
“…In a similar work, Liu and Chen (2015) also investigated the effect of solution chemistry on the interaction of GO, another carbon nanomaterial, with DOPC SLBs and SVLs. They showed that GO deposits on DOPC SLBs in presence of NaCl and CaCl 2 and similar to MWCNTs, presence of Ca 2+ ions resulted in a larger mass and faster deposition kinetics due to their bridging effect.…”
Section: Probing the Interaction Of Nps With Slbs Using Qcm-dmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] For example, the in vitro evaluations of the potential cytotoxic effects of graphene nanomaterials have been actively conducted on different human cell lines, 25,[36][37][38][39][40][41] investigations have attributed the cytotoxicity of both graphene and its oxygenated derivative GO on mammalian cells and bacteria to cellular membrane penetration, followed by phospholipid molecule extraction from the lipid bilayer. 42,43 A small number of in vivo studies have also previously demonstrated that after intravenously administered into rats or mice, GO accumulated in lungs for a prolonged period of time, displayed dose-dependent pulmonary toxicity, and caused lung granuloma death. This shows that, while graphene nanomaterials possess tremendous potential for bioapplications, they may also induce undesirable toxicity under certain conditions.…”
Section: Physicochemical Parameters Influencing the Hemotoxicity mentioning
confidence: 99%